Kekerasan dalam Rumah Tangga pada Perkawinan Usia Anak di Wilayah Kota Bengkulu - Dwi Putri, Malia (UNIB Press, 2023)
The age of marriage has an impact on household problems that can arise such as moral crises, disharmony, and irresponsibility which will have a high potential to experience domestic violence. In principle, child marriage brings a lot of harm and not a few ends in divorce. Based on this paradigm, child marriage must be prevented. The aim of the research is to identify, describe, and analyze the factors that cause domestic violence that occurs in child marriages, forms of domestic violence (domestic violence) that occur in child marriages, efforts to prevent child marriages. The nature of the research is descriptive and the legal research approach uses an empirical legal approach. The results of the study: the causes of domestic violence (KdRT) that occur in child marriages in the Bengkulu City area, namely their life is not sufficient (economic factors), excessive jealousy, excessive emotion or hardness, this is influenced by internal and external factors . Forms of domestic violence (KdRT) that occur in child marriages are physical violence, emotional violence, economic violence. The efforts to prevent child marriage are through cultivating an understanding related to maturing the age of marriage and the dangers of child marriage as a trigger for domestic violence.